Collaborating with Industry to Enhance Financial Planning and Accounting Education - Mark Brimble; Craig Cameron; Brett Freudenberg; Campbell Fraser; Kirsten MacDonald (Australasian Accounting, Business and Finance Journal, 2012)
Higher education is integral to the professionalisation of financial planning in Australia. However, the traditional separation between ‘content’ and ‘practice’ in tertiary curriculum does not necessarily equip students with the skills required to apply the content in a professional context. Contextualisation of the financial planning curriculum requires collaboration between higher education institutions and the profession to develop authentic learning environments, such as work-integrated learning (WIL). This paper describes the collaboration by one Australian university to develop a professionally integrated Financial Planning and Accounting degree and provides evidence of its impact from an industry perspective. The results reveal a high level of industry satisfaction with the degree, substantial professional integration, as well as the development of students’ professional skills. Students also developed an improved impression of the university, its students and its staff.
Keywords: Financial planning education; generic skills; work integrated learning; internship; collaboration